Penambahan Suplemen Zinc (Zn) pada Sinkronisasi Estrus Kambing Ras Campuran - Muhammad Rosyid Ridlo; Agung Budiyanto (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
The aim of this study was to understand the effect of using Zinc (Zn) to oestrous synchronization in Indonesian Mixed Breed Goat. The number of 12 does aging 24-36 months and a buck were used in this experiment in order to natural copulation purpose. The experimental animals were devided into 2 groups. The first group was given oestrous synchronization using polyurethane sponge which contained of medroxi progesterone acetate 60 mg through intra vaginal for 14 days (control). The Second group was synchronized in the same method as the first group and supplemented with Zn 20 mg/head by peroral. The does that have been oestrous then mated naturally. The experimental results indicate the number of natural copulation in second group was higher than control (83% vs 50%). Oestrous uniformity occurred in both groups. The Oestrous onset in second group was earlier than control (36 vs 48 jam) and duration of oestrous was longer than control (12 vs 48 jam).Maximum oestrous quality score was higher than control (7.17±0.75 vs 6.67±0.52). The conclusion is the addition of Zn Supplement improves the quality of oestrous during oestrous synchronization by intra vaginal polyurethane sponge which contained of medroxi progesterone acetate 60 mg in Indonesian mixed breed goat.